2006
DOI: 10.1002/smll.200500294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Size‐Dependent Magnetic Properties of Monodisperse EuS Nanocrystals

Abstract: Size-controllable monodisperse nanomaterials have been studied intensively due to their fundamental scientific interest and potential technological applications. [1] So far, the monodisperse magnetic nanocrystals, such as Fe, Co, FePt, CoPt, Fe 2 O 3 , Fe 3 O 4 , have been synthesized [2] for possible applications in magnetic data storage, ferrofluids, refrigeration systems, medical imaging, drug targeting, and catalysis. [3] Compared with a number of works done on these nanomagnetic metals and metal oxides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 51 publications
2
106
1
2
Order By: Relevance
“…[62] Nanocrystalline EuS has been the subject of ongoing experimental and theoretical investigation because of its interesting magnetic properties. [63][64][65] EuS exhibits ferromagnetic behavior with a Curie temperature of 16 K and is a candidate model system for demonstrating spintronics or optoelectronic phenomena. It is also an example of a bulk semiconductor material that displays a distinct absorption band, found at $2.35 eV, Figure 3.…”
Section: Interesting Band Structure Effects In Bulk Nanocrystalsmentioning
confidence: 99%
“…[62] Nanocrystalline EuS has been the subject of ongoing experimental and theoretical investigation because of its interesting magnetic properties. [63][64][65] EuS exhibits ferromagnetic behavior with a Curie temperature of 16 K and is a candidate model system for demonstrating spintronics or optoelectronic phenomena. It is also an example of a bulk semiconductor material that displays a distinct absorption band, found at $2.35 eV, Figure 3.…”
Section: Interesting Band Structure Effects In Bulk Nanocrystalsmentioning
confidence: 99%
“…[14] During the past a few years, several research groups reported various routes to prepare the EuX NCs, such as with high temperature reduction, thermal or optical decomposition of single-source precursors, and a liquid-phase synthesis. [15][16][17][18] However these methods usually required special instruments and extra ligands for Eu 3+ , which were time-consuming with the product; meanwhile, the resulting EuX NCs exhibited poor optical and magnetic properties, with little potential in applications.…”
mentioning
confidence: 99%
“…Until now, great efforts have been devoted to the controlled synthesis of nanostructured materials as their properties are dependent on their size [15], morphology [16], phase purity [17] and surface characteristics [18], as well as their chemical compositions [4,5,[9][10][11]18].…”
Section: Introductionmentioning
confidence: 99%